Prospects and Challenges of Induced Pluripotent Stem Cells in Equine Health - Donadeu, F. Xavier; Esteves, Cristina L. (Frontiers in Veterinary Science, 2015)
Pluripotent stem cells (PSCs) hold, through the capacity to differentiate into virtually all body cell types, unprecedented promise for human and animal medicine. PSCs are naturally found in the early embryo, and in rodents and humans they can be robustly harvested and grown in culture in the form of embryonic stem cells (ESCs), however the availability of ESCs from horses is limited. ES-like cells named induced pluripotent stem cells (iPSCs) can be derived in vitro by transcription factor-mediated reprogramming of adult cells. As such, iPSCs can be generated in a patient-specific manner providing unmatched potential for tissue transplantation and in vitro disease modelling. In humans, clinical trials using iPSC-derived cells are already taking place and the use of in vitro iPSC models has identified novel mechanisms of disease and therapeutic targets. Although to a more limited extent, iPSCs have also been generated from horses, a species in which, after humans, these cells are likely to hold the greatest potential in regenerative medicine. Before a clinical use can be envisioned, however, significant challenges will need to be addressed in relation to the robust derivation, long-term culture, differentiation and clinical safety of equine iPSCs. Towards this objective, recent studies have reported significant improvement in culture conditions and the successful derivation for the first time of functional cell types from equine iPSCs. Given the wide range of exciting applications they could have, it is hoped future research will make the biomedical promise of iPSCs a reality not only for humans but also horses.